Synthesis and Characterization of some Nano Adsorbents and their Application in Removal of selected Metallic Pollutants from Aqueous Solutions - Gusain, Deepak (IIT(BHU), Varanasi, 2016)
Abstract is available in the attachment
This Thesis Submitted by PHD Scholar IIT(BHU), Varanasi & Supervised by Prof. Y. C. Sharma & V. K. Singh
Keywords: Synthesis; Nano Adsorbents; Aqueous; Metallic Pollutants; Solutions